1976
DOI: 10.1128/jvi.20.2.535-538.1976
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage PBS2-induced inhibition of uracil-containing DNA degradation

Abstract: Degradation of uracil-containing DNA by Bacillus subtilis extracts and its inhibition after infection by the uracil-containing DNA phage PBS2 have been investigated to resolve differences between the published reports of Tomita and Takahashi (1975) and Friedberg et al. (1975, 1976). The product of hydrolysis of PBS2 DNA, tritium labeled in its uracil and cytosine residues, is solely uracil and not deoxyuridine. The degrading activity is completely inhibited within 7 min after PBS2 infection, before any other k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…Thus, the relative plaque-forming efficiencies, the kinetics of one-step growth, the burst sizes, and, the lengths of the progeny single-stranded DNAs were the same in these two hosts. These results can be explained in terms of the findings of several workers (2,4,6,18) that phage PBS1 produces an inhibitor of the host Nglycosidase shortly after infection. In our own experiments, the N-glycosidase activity of the 168T host cells decreased more than 50% within 5 min and diminished completely within 10 min after infection.…”
Section: Resultssupporting
confidence: 52%
“…Thus, the relative plaque-forming efficiencies, the kinetics of one-step growth, the burst sizes, and, the lengths of the progeny single-stranded DNAs were the same in these two hosts. These results can be explained in terms of the findings of several workers (2,4,6,18) that phage PBS1 produces an inhibitor of the host Nglycosidase shortly after infection. In our own experiments, the N-glycosidase activity of the 168T host cells decreased more than 50% within 5 min and diminished completely within 10 min after infection.…”
Section: Resultssupporting
confidence: 52%
“…Recent in vitro studies have shown that the Mu mom' DNA is at least partially resistant to the action of several type II restriction endonucleases, whereas Mu mom-DNA is sensitive. By comparing and aligning the recognition sequences of restriction enzymes whose cleavage is affected by the Mom function, we deduced a consensus recognition sequence for Mom of 5'-C/G-A-G/C-N-Py-3' (63). By checking the recognition sequences of E. coli restriction enzymes (Table 1), one can see that the sequences for EcoPl, EcoP15, EcoB, and EcoK all overlap with the Mom recognition sequence, but that the EcoRI sequence differs completely, so that the in vivo protection against the first group of restriction endonucleases, but not against EcoRI, is understandable.…”
Section: Mumentioning
confidence: 99%
“…This potentially mutagenic lesion is normally removed by an enzyme called uracil-N-glycosylase, which cleaves the N-glycosidic bond (81). Phages like PBS2, whose DNA normally contains uracil instead of thymine, direct the synthesis of a protein that inhibits the host uracil Nglycosylase (35,62,63,123). The evolution of such an inhibitor demonstrates the importance of the unusual base uracil for the phage.…”
Section: Unusual Bases In Phage Dnamentioning
confidence: 99%
“…Cellular utilisation of Ung activity is not limited to its role in DNA repair (Figure 4), thus Ung is observed to play important roles in other key cellular programs, such as innate cellular immunity as a frontline defence against viral pathogens. The importance of this role for Ung is underlined by the fact that diverse virus lineages, whether targeting prokaryotes or eukaryotes, actively silence Ung at the mRNA or/and at the protein level [41,[53][54][55][56][57][58][59][60]. It would appear that viruses, in general, are sensitive to uracil in DNA for varying reasons.…”
Section: The Ung-type Uracil-dna Glycosylase Is Central To the Host Pmentioning
confidence: 99%